Insulated molecular wires: inhibiting orthogonal contacts in metal complex based molecular junctions - Al-Owaedi,OA; Bock,S; Milan,DC; Oerthel,M-C; Inkpen,MS; Yufit,DS; Sobolev,AN; Long,NJ; Albrecht,T; Higgins,SJ; Bryce,MR; Nichols,RJ; et al. (Nanoscale, 2017)
Metal complexes are receiving increased attention as molecular wires in fundamental studies of the transport properties of metal|molecule|metal junctions. In this context we report the single-molecule conductance of a systematic series of d8 square-planar platinum(II) trans-bis(alkynyl) complexes with terminal trimethylsilylethynyl (C[triple bond, length as m-dash]CSiMe3) contacting groups, e.g. trans-Pt{C[triple bond, length as m-dash]CC6H4C[triple bond, length as m-dash]CSiMe3}2(PR3)2 (R = Ph or Et), using a combination of scanning tunneling microscopy (STM) experiments in solution and theoretical calculations using density functional theory and non-equilibrium Green's function formalism. The measured conductance values of the complexes (ca. 3–5 × 10−5G0) are commensurate with similarly structured all-organic oligo(phenylene ethynylene) and oligo(yne) compounds. Based on conductance and break-off distance data, we demonstrate that a PPh3 supporting ligand in the platinum complexes can provide an alternative contact point for the STM tip in the molecular junctions, orthogonal to the terminal C[triple bond, length as m-dash]CSiMe3 group. The attachment of hexyloxy side chains to the diethynylbenzene ligands, e.g. trans-Pt{C[triple bond, length as m-dash]CC6H2(Ohex)2C[triple bond, length as m-dash]CSiMe3}2(PPh3)2 (Ohex = OC6H13), hinders contact of the STM tip to the PPh3 groups and effectively insulates the molecule, allowing the conductance through the full length of the backbone to be reliably measured. The use of trialkylphosphine (PEt3), rather than triarylphosphine (PPh3), ancillary ligands at platinum also eliminates these orthogonal contacts. These results have significant implications for the future design of organometallic complexes for studies in molecular junctions.